Örgütsel Kayıtsızlık Ölçeğinin Türkçe Formunun Geçerlik ve Güvenirlik Çalışması - Uzunbacak, Hasan Hüseyin; Erhan, Tuğba; Akçakanat, Tahsin (Muş Alparslan Üniversitesi, 2021)
The concept of organizational indifference is stated as the feeling of estrangement of employees towards the organization’s different aspects and absence of commitments in time. Organizational indifference, which has been considered among the current variables both in the field of organizational behavior and human resources recently, will provide significant contribution to the literature. The aim of this study is to adapt the Organizational Indifference Scale into Turkish and perform the validity and reliability analyses. The sample of the study comprised of 248 employees who work in the retail industry in Isparta. Within the scope of the study, it is applied to the Social and Humanity Sciences Ethics Committee of T.C. Süleyman Demirel University and the approval of the research is taken on 12.28.2020 with the number of 2020/9. As a result of confirmatory factor analysis, the model showed acceptable fit to the data. Internal consistency reliability coefficients of the scales’ dimensions were calculated between .68 and .85. The results of the item analysis indicated that the corrected item-total score correlations of the subscales varied between .33 and .68. Besides, it was determined that the adapted scale had criterion-related validity. As a result of the correlation analysis, it was found out that the sub-dimensions of the Organizational Indifference Scale had a negative relationship with affective commitment, and a positive relationship with turnover intention. Based on these findings, it was considered a valid and reliable measurement tool that can be used in the field of organizational behavior.

Örgütsel Kayıtsızlık kavramı, örgüt çalışanlarının farklı boyutlarda örgütlerine karşı yabancılaşması ve zamanla örgüte olan bağlılıklarının ortadan kaybolması şeklinde ifade edilebilir. Son yıllarda örgütsel davranış ve insan kaynakları alanında güncel kavramlardan birisi olarak ifade edilen örgütsel kayıtsızlığın, bir ölçme aracıyla ölçülebilmesi alan yazın açısından önemli bir kolaylık sağlayacaktır. Bu araştırmanın amacı, Örgütsel Kayıtsızlık Ölçeği’ni Türkçeye uyarlamak ve geçerlik, güvenirlik analizlerini gerçekleştirmektir. Araştırmanın örneklemi, Isparta ilinde perakende sektöründe görev yapan 248 çalışandan oluşmaktadır. Çalışma kapsamında T.C. Süleyman Demirel Üniversitesi Sosyal ve Beşerî Bilimler Etik Kuruluna müracaat edilmiş, 28.12.2020 tarihinde kurulun 2020/9 sayılı kararı ile araştırmanın yapılması uygun bulunmuştur. Yapılan doğrulayıcı faktör analizi sonuçları, modelin kabul edilebilir seviyede uyum verdiğini göstermiştir. Ölçeğin boyutlarının iç tutarlık güvenirlik katsayıları .68 ile .85 arasında hesaplanmıştır. Madde analizi sonucunda alt ölçeklerin düzeltilmiş madde-toplam puan korelasyonlarının .33 ile .68 arasında değiştiği görülmüştür. Ayrıca, uyarlaması yapılan ölçeğin ölçüt bağıntılı geçerliğe sahip olduğu belirlenmiştir. Yapılan korelasyon analizi sonucunda Örgütsel Kayıtsızlık Ölçeği’nin alt boyutlarının, duygusal bağlılıkla negatif, işten ayrılma niyeti ile pozitif yönlü ilişkileri bulunmuştur. Bu bulgulara dayanarak, ölçeğin örgütsel davranış alanında kullanılabilecek, geçerli ve güvenilir bir ölçme aracı olduğu düşünülmektedir.
Validity and Reliability Study of the Turkish Version of the Organizational Indifference Scale
anemon
Keywords: Indifference; Organizational Indifference; Scale Validation; Kayıtsızlık; Örgütsel Kayıtsızlık; Ölçek geçerleme